Effect of microelectrode array spacing on the growth of platinum electrodeposits and its implications for oxygen sensing in ionic liquids - Lee, Juni; Mullen, Jesse W.; Hussain, Ghulam; Silvester-Dean, Debbie (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Microelectrodes are popular in electroanalysis because radial diffusion to the electrodes results in high current density. The current can then be multiplied by increasing the number of electrodes in an array configuration, allowing for low concentrations of analyte species to be detected. Microelectrode arrays are usually designed so that individual microelectrodes (in a hexagonal arrangement) are sufficiently spaced, ensuring that diffusion layers do not overlap during electrochemical experiments, but are not too far separated so that space is wasted. In this study, the effect of microelectrode spacing has been investigated for platinum deposition into the microholes of commercially available microarray devices. The microarrays have 91 recessed microelectrodes, 10 µm in diameter, 3.3 µm depth, but with four different centre-to-centre spacings of 80, 60, 40 and 20 µm (8, 6, 4 and 2 times the diameter). A 300 s deposition time in an aqueous hexachloroplatanic acid solution was used to deposit three-dimensional Pt structures into the array. The size of the deposits systematically decreased as the electrode spacing became smaller, as a result of overlapped diffusion layers during the deposition process. The modified microarrays were then used for the sensing of a model analyte (oxygen) in a room temperature ionic liquid, with the larger deposits (with larger surface areas) giving higher current responses. However, current densities were found to be quite comparable for all spacings. The 2 times diameter separation can theoretically fit 16 times the number of electrodes into the same area of the underlying Au electrode compared to the 8 times separation. Therefore, it should be possible to design devices that have significantly higher electrode density, which can maximise the overall current and lead to better analytical performances. This work shows that it is important to consider both the geometry and electrode separation for microarrays when used in electrodeposition and for electroanalytical applications.